2022
DOI: 10.3389/fimmu.2022.841188
|View full text |Cite
|
Sign up to set email alerts
|

Maltodextrin Consumption Impairs the Intestinal Mucus Barrier and Accelerates Colitis Through Direct Actions on the Epithelium

Abstract: Food additives are common components of processed foods consumed in a Western diet. In inflammatory bowel disease patients, some diets that exclude food additives improved clinical disease parameters, suggesting a link between food additives and disease pathogenesis. Food additives also enhanced disease severity in mouse colitis models through incompletely described mechanisms. This study examined the mechanisms by which the food additive maltodextrin (MDX) alters the development of colitis in a murine model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The levels of flagellin and LPS were enhanced after treatment with emulsifiers. Metagenomics results have demonstrated an enrichment of genes related to flagella and bacterial motility in the gut microbiome 59,62 . Research conducted on mice has also shown that the consumption of emulsifiers can alter the composition of the gut microbiota, increase intestinal inflammation, and promote metabolic disorders 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The levels of flagellin and LPS were enhanced after treatment with emulsifiers. Metagenomics results have demonstrated an enrichment of genes related to flagella and bacterial motility in the gut microbiome 59,62 . Research conducted on mice has also shown that the consumption of emulsifiers can alter the composition of the gut microbiota, increase intestinal inflammation, and promote metabolic disorders 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we saw that genes related to the metabolism maltodextrin—a synthetic starch which has increased dramatically in abundance in Western diets in recent years [59, 60]—appeared to be under selection in several species. As consumption of maltodextrin has been implicated experimentally in the onset of colitis [61, 62], these selective sweeps may have implications for human health. More broadly, future work in which systematic scans of adaptation are performed in a variety of cohorts may reveal genetic loci in the microbiome that are especially relevant to certain human conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent researchers have found that factors that affect the intestinal mucus barrier, such as food intake [26,27], in ammatory bowel diseases (IBDs) [28,29], and Helicobacter pylori infection [30], are key determinants of microbiome composition, therefore directly in uence host GI health, and has been reviewed extensively elsewhere. However, environmental factors known to in uence the intestinal mucus barrier have been comparatively neglected in the microbiome eld.…”
Section: Discussionmentioning
confidence: 99%